Assessment of factors influencing retention in the Philippine National Rural Physician Deployment Program - Leonardia, Juan Alfonso; Prytherch, Helen; Ruppel, Andreas (BMC health services research, 2012)
The ‘Doctors to the Barrios’ (DTTB) Program was launched in 1993 in response to the shortage of doctors in remote communities in the Philippines. While the Program has attracted physicians to work in such areas for the prescribed 2-year period, ongoing monitoring shows that very few chose to remain there for longer and be absorbed by their Local Government Unit (LGU). This assessment was carried out to explore the reasons for the low retention rates and to propose possible strategies to reverse the trend. A mixed methods approach was used comprising a self-administered questionnaire for members of the current cohort of DTTBs, and oral interviews with former DTTBs. Among former DTTBs, the wish to serve rural populations was the most widely cited motivation. By comparison, among the current cohort of DTTBs, more than half joined the Program due to return of service obligations; a quarter to help rural populations, and some out of an interest in public health. Those who joined the Program to return service experienced significantly less satisfaction, whilst those who joined out of an interest in public health were significantly more satisfied with their rural work. Those who graduated from medical schools in the National Capital Region were significantly more critical about their compensation and perceived there to be fewer options for leisure in rural areas. With regard to the factors impeding retention, lack of support from the LGU was most frequently mentioned, followed by concerns about changes in compensation upon absorption by the LGU, family issues and career advancement. Through improved collaboration with the Department of Health, LGUs need to strengthen the support provided to DTTBs. Priority could be given to those acting out of a desire to help rural populations or having an interest in public health, and those who have trained outside of the National Capital Region. Whether physicians should be able to use the Program to fulfil return service obligations should be critically assessed.